Answer:
B = A/5h - b; You could use
B = (A - 5hb)/5h This just puts everything over a common denominator.
Step-by-step explanation:
A = 5h (B + b) Divide both sides by 5h
A/5h = B + b Subtract b from both sides.
A/5h - b = B
5 minutes
32/160 = 0.2 mile/min
0.2x = 1
0.2x/0.2 = 1/0.5
x = 5
5 minutes
Answer: E) 450g and F) 100g
Step-by-step explanation:
A pound is approximately <em>0.4535 kilogrammes</em>, so <em>453,5 grammes</em>. With this information, we can determine that answers E (450 grammes) and F ( 100 grammes) are the only correct ones.
Answer:
6x +19
Step-by-step explanation:
6(x +2) +7
distribute the 6 (multiply 6*x and 6*2)
6x + 12
add the 7 to the 12
=6x + 19
If you would like to solve the equation 3 * (3 * x - 1) + 2 * (3 - x) = 0, you can calculate this using the following steps:
3 * (3 * x - 1) + 2 * (3 - x) = 0
3 * 3 * x - 3 * 1 + 2 * 3 - 2 * x = 0
9 * x - 3 + 6 - 2 * x = 0
7 * x + 3 = 0
7 * x = - 3 /7
x = - 3/7
The correct result would be - 3/7.